The role of mononuclear phagocyte system in IgA nephropathy: pathogenesis and prognosis - Liu, Yiwen; Gong, Yan; Xu, Gaosi (Frontiers in Immunology, 2023)
Although “multiple hits” theory is widely accepted pathogenesis in IgA nephropathy (IgAN), increased evidence suggested that the mononuclear/macrophage system played important roles in the progression of IgAN, however, the exact mechanism was unclear. In present study, we explored 1067 patients in 15 studies and found the number of macrophages per glomeruli was positively related with the degree of hematuria, and the macrophages in glomeruli were mainly related to mesangial proliferation (M) in renal biopsy. In tubulointerstitial, macrophages were significantly paralleled to tubulointerstitial α-SMA and NF-kB expression, tubulointerstitial lesion, tubule atrophy/interstitial fibrosis (T) and segmental glomerulosclerosis (S). In glomeruli and tubulointerstitial, M1 accounted for 85.41% in the M classification according to the Oxford MEST-C, while in the blood M1 accounted for 100%, and the patients with low CD89+ monocytes mean fluorescence intensity displayed more sever pathological characteristics (S1 and T1-2) and clinical symptoms. M1 macrophages were associated with pro-inflammatory in acute phase, however, M2 (CD163+) macrophages participated in tissue repair and remodeling, which correlated with chronic inflammation. In glomeruli, M2 macrophages activated glomerular matrix expansion by secreting cytokines such as tumor necrosis factor-α (TNF-α) and tumor necrosis factor-β (TGF-β) etc., and M0 (CD68+) macrophages stimulated glomerular hypercellularity. In tubulointerstitial, M2 macrophages played pivotal roles in renal fibrosis and sclerosis. It assumed that macrophages acted as antigen presenting cells to activate T cells and relieved diverse cytokines to stimulate inflammatory response. Macrophages infiltrating glomeruli destroyed the integrity of podocytes through the mesangio-podocytic-tubular crosstalk as well as the injury of tubule.